If PLOS ONE were really 101 different specialized journals: A proposed approach to the evaluation of multidisciplinary megajournals - Repiso, Rafael; Moreno Delgado, Alicia; Torres-Salinas, Daniel (Learned Publishing, 2020)
This paper assesses the impact of the various topic-based categories covered by the megajournal PLOS ONE. We analyse the articles published in PLOS ONE in 2016 and 2017 by classifying them according to the Web of Science Journal Citation Report categories. We have identified 101 substantial categories, 86 of which belong to the Science Citation Index Expanded and 15 to the Social Science Citation Index Expanded. 'Biochemistry & Molecular Biology' stands out as the most prolific category, accounting for 9% of the manuscripts. On calculating the impact factor of each topic-based category as if it were an independent journal, we found that 28.7% of them would be placed in the first quartile of their corresponding field. Among the highest-ranked journals, 'Palaeontology' and 'Nursing' stand out as they would be ranked in the first decile of their respective categories. About 69% of the categories would be in the second and third JCR quartiles, and only two would be in the fourth. This study indicates the need to assess the impact of papers published in megajournals by topic-based category in order to accurately quantify the impact they have on their specific fields.
Keywords: JCR; Scopus